Understanding Farmers’ Adoption Decisions for New Cash Crops: Evidence from Xishuangbanna in Tropical China - Zhang, Le; Kono, Yasuyuki; Hua, Xiaobo; Zheng, Lin; Zhou, Rui (Problemy Ekorozwoju, 2017)
On a global basis, cash cropping is usually identified as an important enterprise undertaken by farmers to increase incomes. However, the responses of farmers to these new enterprises vary greatly. Through a case study of a Dai village in Xishuangbanna, China, this paper examines how farmers make decisions about adopting new cash crops by focusing on the farm economy and land conditions. The results show that farmers did not adopt watermelons due to poor irrigation and accessibility conditions, and then they did not adopt bananas due to a transient collapse of banana market, induced by a rumor suggesting that eating bananas causes cancer. Consequently, although these non-adopters benefited from commercial exchanges with external businessmen in terms of ecological experiments and management diversification, and leasing lowlands to external businessmen is a livelihood choice that is based on the outcome of the farmer’s trade-off between profitability and risk, they missed opportunities to substantially increase incomes through cash cropping, as evidenced by the success of the farmers who adopted the cash crops. These findings suggest that the government ought to design tailored extension programs for villages, implement efficient refutation strategies to prevent rumor-induced market collapse and promote extension services as early as possible in the initial stages of transition to cash cropping.